Transhumanism and Theological Anthropology: A Theological Examination of Transhumanism - Jung, Daekyung (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2022)
Humans are now entering a post-human era. Through technological advancements and their applications for humans themselves, humans as homo sapiens might change into a different species. Depending on individual decisions about whether to embrace certain technologies, the co-existence of humans and post-humans is also possible. Christians and theologians must ponder this trajectory for the technology will affect all domains, including religions, in society at large. In this regard, this article introduces and examines transhumanism. Transhumanism is a movement based on the convergence of ideology and scientific technology which aims to liberate humans from their biological constraints (i. e., disease, aging, and death), thereby bringing about human well-being. This article argues that the transhumanist ideology should be critically examined while its technology can be embraced and even supported from a theological perspective because this ideology determines the direction of technological advancement and application. Regarding ideological problems, I highlight transhumanists' disembodiment propensity, optimistic belief in the progress of human civilization, and individualism. These features are embedded in and originate from transhumanism’s succession of classical humanism and the Enlightenment. If these features are not rectified, transhumanism and its technology might repeat disastrous incidents in human history such as eugenics and exacerbate social inequality. As a theologian, I critically examine the ideological features of transhumanism, proposing an alternative understanding with regard to human beings and existence. This effort helps to remedy potential problems of transhumanism in the future, relieve anxiety relating to these problems, and prepare a dialogue between transhumanism and Christian theology. This dialogue will eventually contribute to the robust development of transhumanism and the opening of a new era of the post-human.